Perahu Sandeq: Warisan Suku Mandar yang Terancam Punah oleh Modernisasi - Nianty, Dara Ayu; Asbara, Nurkhalik Wahdanial; Z, Nurhaeda; Ridwan, Ridwan; Bahasoan, Shandra; Rahmah, Rahmah; Khalik, Abd; Salnia, Salnia (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
Abstract Indonesia, with its rich culture and diverse traditions, has become the center of attention of the world. One of the unique and interesting cultural riches is the existence of the traditional Sandeq boat owned by the Mandar Tribe in West Sulawesi. The Sandeq boat is a cultural heritage that is the identity and pride of the Mandar people, but currently its existence is endangered due to the strong modernization current. The Mandar tribe, who inhabit the western coastal region of West Sulawesi, has a long history in the tradition of sailing and traditional boat making. This research uses a qualitative approach to deeply understand the phenomena related to the Sandeq Boat as a heritage of the Mandar Tribe. The Sandeq boat is not just a means of transportation, but also a symbol of the cultural identity of the Mandar Tribe which is rich in traditional values. However, the process of modernization and globalization has had a significant impact on the sustainability of this cultural heritage. The decline in the interest of the younger generation in learning the techniques of making and using the Sandeq Boat, as well as the emergence of modern transportation alternatives, are the main factors that threaten its preservation. Overall, to ensure the sustainability of the Sandeq Boat as a cultural heritage, closer collaboration is needed between the community, the government, and related institutions. Through this collective effort, it is hoped that the Sandeq Boat can continue to be alive and relevant, as well as become an integral part of the identity and pride of the Mandar Tribe in the midst of the ever-growing modernization current.Keywords: Sandeq boats, Heritage, Extinct, ModernizationAbstrak Indonesia, dengan kekayaan budaya dan tradisi yang begitu beragam, menjadi pusat perhatian dunia. Salah satu kekayaan budaya yang unik dan menarik adalah keberadaan perahu tradisional Sandeq yang dimiliki oleh Suku Mandar di Sulawesi Barat. Perahu Sandeq merupakan warisan budaya yang menjadi identitas dan kebanggaan masyarakat Mandar, namun saat ini keberadaannya terancam punah akibat arus modernisasi yang begitu kuat. Suku Mandar, yang mendiami wilayah pesisir barat Sulawesi Barat, memiliki sejarah panjang dalam tradisi pelayaran dan pembuatan perahu tradisional. Penelitian ini menggunakan pendekatan kualitatif untuk memahami secara mendalam fenomena yang berkaitan dengan Perahu Sandeq sebagai warisan Suku Mandar. Perahu Sandeq bukan hanya sekadar alat transportasi, melainkan juga simbol identitas budaya Suku Mandar yang kaya akan nilai-nilai tradisional. Namun, proses modernisasi dan globalisasi telah memberikan dampak signifikan terhadap keberlangsungan warisan budaya ini. Penurunan minat generasi muda dalam mempelajari teknik pembuatan dan penggunaan Perahu Sandeq, serta munculnya alternatif transportasi modern, menjadi faktor utama yang mengancam pelestariannya. Secara keseluruhan, untuk memastikan keberlanjutan Perahu Sandeq sebagai warisan budaya, dibutuhkan kolaborasi yang lebih erat antara masyarakat, pemerintah, dan lembaga terkait. Melalui upaya kolektif ini, diharapkan Perahu Sandeq dapat terus hidup dan relevan, serta menjadi bagian integral dari identitas dan kebanggaan Suku Mandar di tengah arus modernisasi yang terus berkembang.Kata Kunci: Perahu Sandeq, Warisan, Punah, Modernisasi